Exercise-Induced Circulating microRNAs: Potential Key Factors in the Control of Breast Cancer - Telles, Guilherme Defante; Conceição, Miguel Soares; Vechin, Felipe Cassaro; Libardi, Cleiton Augusto; Mori, Marcelo Alves da Silva; Derchain, Sophie; Ugrinowitsch, Carlos (Frontiers in Physiology, 2022)
Losses in skeletal muscle mass, strength, and metabolic function are harmful in the pathophysiology of serious diseases, including breast cancer. Physical exercise training is an effective non-pharmacological strategy to improve health and quality of life in patients with breast cancer, mainly through positive effects on skeletal muscle mass, strength, and metabolic function. Emerging evidence has also highlighted the potential of exercise-induced crosstalk between skeletal muscle and cancer cells as one of the mechanisms controlling breast cancer progression. This intercellular communication seems to be mediated by a group of skeletal muscle molecules released in the bloodstream known as myokines. Among the myokines, exercise-induced circulating microRNAs (c-miRNAs) are deemed to mediate the antitumoral effects produced by exercise training through the control of key cellular processes, such as proliferation, metabolism, and signal transduction. However, there are still many open questions regarding the molecular basis of the exercise-induced effects on c-miRNA on human breast cancer cells. Here, we present evidence regarding the effect of exercise training on c-miRNA expression in breast cancer, along with the current gaps in the literature and future perspectives.